Utilization of Projector Technology in 21st Century Learning: What is the Impact on Student Learning Outcomes? - Sari, Idas Agustianti; Zulaikha, Siti; Puska, Noviliana; Norza, Mardiana (International Journal of Education and Teaching Zone, 2024)
This research examines the impact of the learning process using projector media on student learning outcomes. This research uses a descriptive qualitative approach. The population in this study were students at SD 73/IX Simpang Sungai Duren, totaling 400 students. The sample in the study used a random sampling technique using the Slovin technique with a precision level of 5%, so the number of respondents in this study was 26 people. Data collection techniques in this research used test questions and observation questionnaire sheets. The results of the research show that student activity is 100% or in the very good category, then student focus is 100% in the very good category and also the level of student understanding is Very Good at 73.08%, and the good category at 26.92% which is also in the very good category. This indicates that the projector can contribute to helping the learning process become better.